PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DI DINAS PERTANIAN KABUPATEN GIANYAR - Nengah Landra; Gde Bayu Surya Parwita; Ni Putu Natasya (VALUES, 2023)
Nowadays, government institutions or organizations are required to improve their performance more effectively and efficiently. Institutions or organizations must also pay attention to human resources to increase effectiveness and efficiency. The quality of its human resources strongly influences the progress of an organization. Human resources are an important factor in an organization or agency. This study aims to determine and analyze the effect of transformational leadership style, motivation and work environment on employee performance at the Department of Agriculture, Gianyar Regency. The number of samples used in the study was 89 people using the saturated sample method. Data collection has been done using a 5-point Likert scale questionnaire. The data analysis technique used multiple linear regression analysis. Hypothesis testing was carried out using the t-test, and the data was tested through the classical assumption test stages. The results showed the transformational leadership style with a regression coefficient of 0.240 and significance to employee performance. Motivation with a regression coefficient of 0.261 and significant to employee performance. The work environment with a regression coefficient of 0.172 is significant to employee performance. It is recommended that leaders look for new ideas, find creative solutions, and provide opportunities for employees to socialize more freely. It is hoped that the agency will complete the work needs of employees.